2022
DOI: 10.1002/ange.202201318
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Alkali Metal Reduction of 1‐Adamantanol by London Dispersion Effects

Abstract: A series of alkali metal 1‐adamantoxide (OAd1) complexes of formula [M(OAd1)(HOAd1)2], where M=Li, Na or K, were synthesised by reduction of 1‐adamantanol with excess of the alkali metal. The syntheses indicated that only one out of every three HOAd1 molecules was reduced. An X‐ray diffraction study of the sodium derivative shows that the complex features two unreduced HOAd1 donors as well as the reduced alkoxide (OAd1), with the Ad1 fragments clustered together on the same side of the NaO3 plane, contrary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Interestingly, our synthetic routes to the anticipated monosubstituted alkali metal 1-adamantoxide (MOAd 1 , M = Li, Na, and K) afforded the three-coordinate species [M(OAd 1 )(HOAd 1 ) 2 ] (Figure 16). 84 The significance of this result illustrates the first example of LD interactions limiting the reduction potential of alkali metals, despite excess metal being employed. Energy decomposition analysis of this complex showed that the Ad 1 fragments afford significant dispersion stabilization (and are therefore good DED ligands): approximately one-third of the calculated total bonding energies could be assigned to dispersion effects within this molecule.…”
Section: Designing Enhanced Ld Effects In Hydrocarbon Ligandsmentioning
confidence: 79%
“…Interestingly, our synthetic routes to the anticipated monosubstituted alkali metal 1-adamantoxide (MOAd 1 , M = Li, Na, and K) afforded the three-coordinate species [M(OAd 1 )(HOAd 1 ) 2 ] (Figure 16). 84 The significance of this result illustrates the first example of LD interactions limiting the reduction potential of alkali metals, despite excess metal being employed. Energy decomposition analysis of this complex showed that the Ad 1 fragments afford significant dispersion stabilization (and are therefore good DED ligands): approximately one-third of the calculated total bonding energies could be assigned to dispersion effects within this molecule.…”
Section: Designing Enhanced Ld Effects In Hydrocarbon Ligandsmentioning
confidence: 79%